Gardneria and Spigelia (Loganiaceae), two genera new to the Flora of Peninsular Malaysia - Julius, Avelinah; Kamin, Imin; Kiew, Ruth; Utteridge, Timothy M.a. (Phytotaxa, 2013)
The genera Gardneria and Spigelia with the discovery of G. ovata from Fraser’s Hill, Pahang, and the tropical American weed, S. anthelmia from Selangor, respectively, are new records for the Flora of Peninsular Malaysia. A full description and taxonomic notes for G. ovata and S. anthelmia in Peninsular Malaysia are presented, and the conservation status is provided for the former species. In addition, the two species are illustrated with colour photographs. An updated generic key for the Flora is provided following the APG III concept of the Loganiaceae.